Neonatal Surgical Emergencies Immediate Referral - Imtiaz Ahmed, Muhammad Akbar, Fazila Hashmi, Roomana Qureshi, Ishrat Rahim, Karim Bux (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This study was conducted to explore the circumstances around which neonates are referred to the pediatric surgical team of Liaquat University Hospital. This influences the surgical management of neonatal emergencies outcome which also turns on awareness of the conditions early diagnosis, proper resuscitation, excellent nursing care, and refer to the proper center, main requirement is the application of a basic neonatal transport unit, whenever necessary these neonates are referred to these centers from wherever they are born. Methods: It is a retrospective descriptive study carried out at Liaquat University Hospital Hyderabad Sindh. This study included every referral neonatal surgical emergency managed by the pediatric surgical team from June 2017 to May 2019. Data were obtained from the patient's files and operation theatre register. This study was conducted over two years from June 2017 to May 2018 in the department of pediatric surgery, Liaquat University of medical health sciences Jamshoro. All the neonates presenting with surgical emergencies were included irrespective of gender, mode of referral, and causes that warrant surgical exploration using sampling of convenience. However, neonates whose carers did not consent to be a part of the study were not included. Inform consent was taken from either of the parents reassuring them about confidentiality, as well as the treatment being unaffected had they chosen to withdraw from a study at any time. The study variables included age, sex, weight, and referral pattern, later data was analyzed using SPSS version 21. Results: Fifty-three neonates were operated in July 2017 to June 2020. Out of 53 neonates, 32 were male and 21 female. The male to female ratio is 1.5:1. Anorectal Malformation 12 (22.6%) Intestinal Atresia 6 (11.3%) and Pneumoperitoneum 5 (9.4%) Hirschsprung's disease 9 (13.2%). Neonates with low birth weight were 5 (9.4%). The basic neonatal referral & transport system was poorer. Age at the time of presentation ranges from 1 to 20 days, a median age was 3 days. Dehydration in mild, moderate, and severe was noted in 38 (71.6%) of the referral neonates. The leading cause of morbidity and mortality was sepsis, mortality was 7 (13.2%). Conclusion: Management of neonatal emergencies the morbidity and mortality were not as high compared to other developing countries. However, improvement in the outcomes will require awareness, early referral to the concerned department, and overcoming difficulties by providing a well-equipped hospital that will provide an outstanding nursing facility and a well-equipped neonatal transportation system. Keywords: Neonatal transport unit, Basic resuscitation, Good nursing care, Neonatal intensive care unit